Procedura wymiaru i wykonania kar dyscyplinarnych wobec skazanych na karę pozbawienia wolności. Część II art. 146 k.k.w.–art. 149 k.k.w. - Kwieciński, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This is the second part of an analysis of issues related to the procedure concerning the levels and enforcement of disciplinary penalties against people serving prison sentences. The author continues his analysis of the issue of sentencing guidelines in disciplinary proceedings. In addition, he tackles the problem of fl exible modification of disciplinary penalties. A lot of attention is devoted to issues concerning statutory limitations and enforcement of disciplinary penalties as well as supervisory assessment of decisions taken in the course of disciplinary proceedings against inmates.
Keywords: kara dyscyplinarna; naruszenie prawa; skazany; wytyczne dotyczące wymiaru kary; przedawnienie postępowania sądowego; nadzór nad postępowaniem dyscyplinarnym; zmiana decyzji o nałożeniu kary; uchylenie kary dyscyplinarnej